Shoreline Changes Analysis of West Pasaman Regency, West Sumatera - Ruzana Dhiauddin; Semeidi Husrin (Pusat Riset Kelautan, 2016)
According to the Hazard Vulnerability Index from BNPB, Indonesia’s National Disaster Management Authority, West Pasaman Regency is one of the area with high vulnerability index located in West Sumatra Province, where all of its coastal areas are adjacent with The Indian Ocean. Coastal erosion and extreme waves have been reported to be the most prominent hazards, beside anthropogenic factors, along West Pasaman coastal area. This research was conducted to estimate the loss of shoreline in the area, and how far it has been shifted over the years. Thus, to achieve the objective, the dynamic of shorelines from different time scales was analyzed using quantitative data (satellite images, Netherland Map of Indonesia, and Indonesia topography map), and the statistical output of DSAS (Digital Shoreline Analysis System). The results were validated by a field survey in 2011 and interviewed local people in 2015. We found the highest erosion, about 8.44 m/y, has been occurring in Sasak Ranah Pasisie District, which separate 14 Km from where the highest accretion, about 23.7 m/y, in Kinali District took place.